Sosialisasi Penerapan Perencanaan Strategis Sistem Informasi dan Teknologi Informasi Untuk Peningkatan Layanan Pendidikan Pada Yayasan KM3 NU Ponorogo - Sri Anardani; Latjuba Sofyana STT; Shendi Teuku Maulana Efendi; Seviannanda Kurniawan (BADAN PENERBIT STIEPARI PRESS, 2024)
The process of implementing good information systems and information technology requires strategic planning that is in line with business goals, so that failure and financial losses in the development of information systems and information technology can be avoided. The KM3 NU Education Foundation of Ponorogo Regency is an education organizing institution. Currently KM3 NU Ponorogo has not utilized information systems and information technology in processing academic and administrative data. This results in difficulties in increasing the productivity of school services. Based on the conditions above, it is necessary to carry out outreach activities, mentoring and FGDs for strategic planning of information systems and information technology so that foundations have guidelines in determining priorities for implementing information systems and information technology. The benefit of this activity is that the foundation can create a roadmap for developing information systems and information technology that supports business processes so that it can compete with competitors